High-performance electrocatalysts for oxygen reduction derived from cobalt porphyrin-based conjugated mesoporous polymers - Wu, Zhong-Shuai (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.